1973
DOI: 10.1002/app.1973.070170410
|View full text |Cite
|
Sign up to set email alerts
|

Modulus reinforcement in elastomer composites. I. Inorganic fillers

Abstract: synopsisThe effect of various inorganic fillers on the storage modulus of four elastomers was determined experimentally. Results are interpreted using the Kerner equation, modified to include a parameter, B, in the volume fraction terms. This factor combines particle size and specific interaction effects, and in theory can be evaluated from energy dissipation measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1

Year Published

1980
1980
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(66 citation statements)
references
References 0 publications
1
64
1
Order By: Relevance
“…The storage modulus Figure 9 shows that the storage modulus increased with increasing concentration of Sm 2 Co 17 particles at all temperatures, which is consistent with earlier reports on filled polymers [4,[27][28][29][30]. The trend in modulus versus filler content at 25°C followed relatively well the lower bound relationship (see Fig.…”
Section: Rheologysupporting
confidence: 89%
“…The storage modulus Figure 9 shows that the storage modulus increased with increasing concentration of Sm 2 Co 17 particles at all temperatures, which is consistent with earlier reports on filled polymers [4,[27][28][29][30]. The trend in modulus versus filler content at 25°C followed relatively well the lower bound relationship (see Fig.…”
Section: Rheologysupporting
confidence: 89%
“…This term broadly includes the interfacial forces between the filler and the matrix, the orientation of the matrix in the immediate vicinity of the filler surface, the formation of an "inter'phase", whose properties and dimensions affect the properties of the composite, especially nucleation of crystallization, and other physicochemical phenomena (20).…”
Section: A Tma Measurementsmentioning
confidence: 99%
“…Despite this, the agreement between the equations and the experimental data is usually not satisfactory. It has been suggested that the reason for that may be the fact that the effective volume fraction of partially immobilised material Φ e is greater than the volume fraction of the filler Φf [13]. If we assume that Φe is given by [13] then the agreement between the theoretical description and the experimental results may be achieved.…”
Section: Resultsmentioning
confidence: 92%